Meningkatkan Kemampuan Membaca dan Menulis Berbasis Indigenousasi dengan Media Flash Card - Alfiatus Safa’ah; Nuria Rimadhani M (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
Reading and writing are basic skills that humans must have because these competencies help humans in communicating and carrying out aspects of life. As learners, reading and writing competencies need to be taught as early as possible in preparation for receiving various lessons at school. It can be assumed that students who have not mastered reading and writing skills will not be able to follow the course of learning smoothly. As a result, the learning process will be hampered and learning objectives cannot be achieved. One of the causes of the low ability to read and write in elementary school students is influenced by intelligence factors and the learning process received by students. Indigenization aims to re-express authenticity which is usually native to get to know the local culture where students come from. This kind of cultural theme needs to be introduced to students in learning activities so that students can appreciate local wisdom. At the initial level of elementary school, training on reading and writing skills with a special theme, in this case culture, must be taught regularly, structured and interesting. Therefore, the use of learning media should be considered in developing reading and writing competence. Flash card is one of the effective media to help improve reading and writing skills, especially at the early elementary school level. Card-shaped media with this visual type have pictures and descriptions that can make students more interested in participating in learning. The application of Flash card media in the learning process is accompanied by cooperative strategies so that its use is more effective and can make students more actively involved in learning. With fun activities in the classroom, the goal of improving the reading and writing skills of grade I (one) students will be achieved.